Pellet digestion: a simple and efficient sample preparation technique for LC–MS/MS quantification of large therapeutic proteins in plasma. (January 2012) - Ouyang, Zheng; Furlong, Michael T; Wu, Steven; Sleczka, Bogdan; Tamura, James; Wang, Haiqing; Suchard, Suzanne; Suri, Anish; Olah, Timothy; Tymiak, Adrienne; Jemal, Mohammed
Background: There is a need for a simple and efficient sample preparation technique for LC–MS/MS quantification of large therapeutic proteins in plasma.Results: The sample preparation technique presented here is based upon trypsin digestion of the pellet obtained following precipitation of the protein analyte from plasma. The pellet digestion technique was shown to facilitate efficient digestion of large therapeutic proteins, with concomitant removal of a substantial amount of potentially problematic plasma phospholipids. The technique was successfully applied to a pharmacokinetic study of a large therapeutic protein.Conclusion: This simple sample preparation approach will be beneficial to bioanalytical laboratories engaged in the LC–MS/MS quantification of large therapeutic proteins in biological matrices.